Stimulative Work Valuation Among Real Estate Practitioners in Asia - CASTILLO-MANALASTAS, ROBERTO DEL; CABALLERO, JOHN HENRY R.; MANALASTAS, REBECCA DC.; JR, ROSEIN A. ANCHETA .; JR., REMEGIO M. BERGAMO; MALABAGO, NOLASCO K.; CANONIGO, JULIA T.; TENERIFE, JANINE JOY N.; SUSON, ROBERTO L. (The journal of contemporary issues in business and government, 2021)
Real estate or property production has been recognized as one of Asia's key industries. Based on this significance, the authors assessed the work centrality and working values of real estate practitioners in established Asian countries. Based on the findings, in terms of work centrality, Japan was rated high on work centrality as very important in six life aspects among the five countries, followed by Indonesia, the Philippines, Malaysia, and Myanmar. Findings on work values were all significant among the five countries, headed by Japan, Indonesia, Myanmar, Malaysia, and the Philippines. There is a substantial difference in the perception of work centrality among respondents in five countries, as revealed by Indonesia and Myanmar and Myanmar and Japan. Some countries differ in work values as manifested by Malaysia and Japan, highly significant, like Myanmar and Japan, and the Philippines. Enablers for success in the real estate profession include enterprising and conventional interests and various work values listed by experts in the field. Based on the study's findings, it can be seen that work centrality and work values among the five Asian countries differ from each other. Capability Building Index is now recommended for adoption by the real estate practitioners.